2012
DOI: 10.1111/j.1600-0714.2012.01183.x
|View full text |Cite
|
Sign up to set email alerts
|

Oral human β‐defensin 2 in HIV‐infected subjects with long‐term use of antiretroviral therapy

Abstract: BACKGROUND The objectives of this study were to determine 1) oral hBD2 expression in HIV-infected subjects compared to non-HIV controls, 2) the expression of oral hBD2 in HIV-infected subjects with ART compared with those without ART, and 3) factors associated with the expression of oral hBD2. METHODS Oral examination and punched biopsy on buccal mucosa were performed in HIV-infected subjects with and without ART, and non-HIV individuals. The expression of hBD2 mRNA was determined by quantitative real-time P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 35 publications
(50 reference statements)
0
19
0
Order By: Relevance
“…Nittayananta et al . demonstrated that the levels of human β‐defensin‐2 protein in saliva of HIV‐infected individuals was increased with short‐term use of HAART but decreased with long‐term use of the medication. This change in oral mucosal immunity may result in significant alterations in the composition of oral bacteria, putting HIV‐infected patients at risk of developing oral infections .…”
Section: Discussionmentioning
confidence: 99%
“…Nittayananta et al . demonstrated that the levels of human β‐defensin‐2 protein in saliva of HIV‐infected individuals was increased with short‐term use of HAART but decreased with long‐term use of the medication. This change in oral mucosal immunity may result in significant alterations in the composition of oral bacteria, putting HIV‐infected patients at risk of developing oral infections .…”
Section: Discussionmentioning
confidence: 99%
“…The infection may directly affect the oral epithelium, resulting in the alterations in the cell structure and function that impair the innate immunity and promote colonization and infection by commensal and pathogenic organisms (6, 14, 15). Thus, oral lesions in HIV- infected individuals have been firstly documented since 1981 in a cohort of young homosexual males presenting with Pneumocystis carinii pneumonia (PCP) and concurrent mucosal candidiasis (16).…”
Section: What Are the Effects Of Hiv Infection On Oral Innate Immunity?mentioning
confidence: 99%
“…Many factors may contribution to the differences between the studies such as sample size and cohort effects, as well as types of saliva studied (whole saliva vs. glandular saliva). The levels of hBD-2 proteins in stimulated saliva were also found to be significantly different between HIV-infected patients who received HAART compared to those who were not on the medication (6). These findings suggest that HAART may impair oral epithelial cells functions in innate immunity leading to the alterations of the oral hBD-2 expression (6).…”
Section: What Are the Effects Of Haart On Oral Innate Immunity?mentioning
confidence: 99%
See 2 more Smart Citations